Large‐scale fungal diversity assessment in the Andean Yungas forests reveals strong community turnover among forest types along an altitudinal gradient. Issue 10 (May 2014) - Geml, József; Pastor, Nicolás; Fernandez, Lisandro; Pacheco, Silvia; Semenova, Tatiana A.; Becerra, Alejandra G.; Wicaksono, Christian Y.; Nouhra, Eduardo R.
Abstract The Yungas, a system of tropical and subtropical montane forests on the eastern slopes of the Andes, are extremely diverse and severely threatened by anthropogenic pressure and climate change. Previous mycological works focused on macrofungi (e.g. agarics, polypores) and mycorrhizae in Alnus acuminata forests, while fungal diversity in other parts of the Yungas has remained mostly unexplored. We carried out Ion Torrent sequencing of ITS2 rDNA from soil samples taken at 24 sites along the entire latitudinal extent of the Yungas in Argentina. The sampled sites represent the three altitudinal forest types: the piedmont (400–700 m a.s.l.), montane (700–1500 m a.s.l.) and montane cloud (1500–3000 m a.s.l.) forests. The deep sequence data presented here (i.e. 4 108 126 quality‐filtered sequences) indicate that fungal community composition correlates most strongly with elevation, with many fungi showing preference for a certain altitudinal forest type. For example, ectomycorrhizal and root endophytic fungi were most diverse in the montane cloud forests, particularly at sites dominated by Alnus acuminata, while the diversity values of various saprobic groups were highest at lower elevations. Despite the strong altitudinal community turnover, fungal diversity was comparable across the different zonal forest types. Besides elevation, soil pH, N, P, and organic matter contents correlated with fungal community structure as well, although most of these variables were co‐correlated with elevation. Our data provide an unprecedented insight into the high diversity and spatial distribution of fungi in the Yungas forests.